Analysis The Effectiveness Of Tangerang City Government Communication Through Laksa Feature On The Tangerang Live Application - Satriannisa, Hasna; Rahmawati, Dian Eka (JURNAL TRIAS POLITIKA, 2025)
Government communication has an important role in managing the relationship between the government and the community. The purpose of this study is to analyze the effectiveness of the Tangerang City Government's communication through the LAKSA feature on the Tangerang LIVE application in receiving and responding to complaints, aspirations, and suggestions given by the public. This research uses a qualitative method by utilizing secondary data sourced from publications of government survey results, annual reports on feature management, and other data officially released by the Tangerang City Government, as well as previous journals relevant to the topic of this research discussion. The data obtained was analyzed interactively through four stages, namely data collection, data reduction, data presentation, and conclusion drawing. Effectiveness is seen from several indicators, namely Communication Recipients, message content, timeliness, channel, packaging format, and source. The results showed that that five assessment indicators have been effective, which are the relevant message content, timeliness of the government's response to complaints, adequate digital communication channels, structured application display, and source credibility. However, the message recipient indicator is not optimal due to the low number of feature users. Thus, it can be concluded that the communication carried out by the Tangerang City Government in the LAKSA feature on the Tangerang LIVE application is effective, but the aspect of number of users needs to be improved. This research contributes to strengthening empirical understanding in digital communication literaure, as well as a clearer mapping of the application of communication effectiveness theory and provides practical implications for the government in improving participatory communication strategies.